Bringing Work Back in Islamic Ethics - Possumah, Bayu Taufiq; Abdul Ghafar Ismail 1962-; Shahimi, Shahida (2013)
Religion and work are seldom discussed. The two have caused scholars to question the religion’s role with work. This paper reviews research on the integrate between religion and work by examining issues of concept, definition, measurement, and reviewing research that examines the relationship of work and religion with respect to: different times, types of people, organize human interactions and sources of knowledge. We then discuss the methodological requirement for reintegrating work studies into social institutional theory and indicate what the conceptual payoffs of such integration might be. These payoffs include breaking new conceptual ground, resolving theoretical puzzles and envisioning the nature of new social institutions
Keywords: Ethic; Islam; Work